Risk and Protective Factors of College Students' Psychological Well-Being During the COVID-19 Pandemic: Emotional Stability, Mental Health, and Household Resources - Julia Moeller; Luise von Keyserlingk; Marion Spengler; Hanna Gaspard; Hye Rin Lee; Katsumi Yamaguchi-Pedroza; Renzhe Yu; Christian Fischer; Richard Arum (SAGE Publishing, 2022)
Colleges and universities have increasingly worried in recent decades about college students' well-being, with the COVID-19 pandemic aggravating these concerns. Our study examines changes to undergraduate emotional sentiments and psychological well-being from before to after the onset of the pandemic. In addition, we explore whether certain risk factors (i.e., prior mental health impairments, trait emotional stability) and protective factors (i.e., subjective socioeconomic status, parental education, household resources) predicted students' emotions and their intraindividual changes due to the pandemic onset. We compared experience sampling method data from 120 students from before and after the pandemic onset, examining intraindividual trajectories. There was only little change in students' emotions. Prior mental health impairment and trait emotional stability predicted students' emotions, averaged across time points, but not emotion changes. Few associations with emotions were found for subjective socioeconomic status and parental education, but study-related household resources predicted levels and changes in emotions.